The research of sorbent properties of modified peat of Tomsk region; Международный научно-исследовательский журнал; № 5 (5), ч. 2 - Martynyuk А. Т. (2012, 2012)
Extraction of different components (bitumen) from thermoprocessed up to 200-300°С peat puts the task of searching new alternative decisions of using the obtained remains. They can be used as cheap sorbent materials. The aim of this research is to estimate sorbent properties of peat remains after the extraction bitumen from them.